PENGARUH RISIKO PEMBIAYAAN, PRIMARY RATIO, BOPO, OPPORTUNITY COST DAN RISIKO LIKUIDITAS TERHADAP MARGIN BANK UMUM SYARIAH DI INDONESIA - Windu Tri Prasetio; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
The purpose of this study is to examine the effect of bank margin’s components on bank margin. Those components consist of financing risk, primary ratio, BOPO, opportunity cost, and liquidity risk The population in this study consists of islamic banking Indonesia. Sampling method used is purposive sampling. By using the triwulan report of islamic banking consist of 11 banks during 2012-2014, total population of this study is 132. Linear reggression used to be analysis technique. The empirical result of this study show that financing risk has a possitive and significant effect to bank margin. While BOPO and primary ratio have a negative and significant effect on bank margin. Opportunity cost and liqudity risk have a positive but not significant effect to bank margin..